T Cell Costimulatory and Coinhibitory Pathways in Vascular Inflammatory Diseases - Lichtman, Andrew (Frontiers in Physiology, 2012)
A broad array of evidence indicates that T lymphocytes make significant contributions to vascular inflammation in the setting of atherosclerotic disease, hypertension, autoimmune vasculitis, and other disorders. Experimental data show that costimulatory and coinhibitory pathways involving molecules of the B7-CD28 and TNF-TNFR families regulate T cell responses that promote vascular disease. Antigen presenting cells display both peptide-MHC antigen and costimulators or coinhibitors to T cells. Two major types of antigen presenting cells, dendritic cells and macrophages, are present in significant numbers in the walls of arteries affected by atherosclerosis and arteritis, and some dendritic cells are present in normal arteries. Costimulatory and coinhibitory molecules expressed by these vascular antigen presenting cells can contribute to the activation or inhibition of effector T cells within the arterial wall. Vascular dendritic cells may also be involved in transport of antigens to secondary lymphoid organs, where they activate or tolerize naïve T cells, depending on the balance of costimulators and coinhibitors they express. Costimulatory blockade is already an approved therapeutic approach to treat autoimmune disease and prevent transplant rejection. Preclinical models suggest that costimulatory blockade may also be effective in treating vascular disease. Experiential data in mice show that dendritic cells pulsed with the appropriate antigens and treated in a way that reduces costimulatory capacity can reduce atherosclerotic disease, presumably by inducing T cell tolerance. Progress in treating vascular disease by immune modulation will require a more complete understanding of the functions of different costimulatory and coinhibitory pathways and the different subsets of vascular antigen presenting cells involved.